Penerapan model pembelajaran STAD dalam pembelajaran IPA untuk meningkatkan minat dan hasil belajar sekolah dasar - Hermawan; Yeni Haerani (JURNAL PENDIDIKAN DAN SAINS, 2023)
The study aims to determine interest and student learning outcome by using the model system of Student Teams Achievement Division in science on the material of the human respiratory system. The subjects of research is students in class V elementary school Barugbug 1, which amount to 40 students consist of 21 male and 19 female. The research was conducted start from March until May 2022. The method of this research is classroom action research. That still passive and the learning process is still going on the a classical or teacher as the source of the material, in the first cycle began to look student activeness tought not a whole. The result of the post test is 78. 63 and it in creases in the second cycle by 89. 12, Students are more active, respons and mutual cooperation in cycle II, interest questionnaire result increased from 57. 5 cycle I to 80. 62 in cycle II.